(untitled) (PAKISTAN JOURNAL OF LAW, ANALYSIS AND WISDOM, 2024)
This qualitative research study examines the extensive impacts of climate change on the residents of Swat, Khyber Pakhtunkhwa, focusing on its socio-economic and psychological ramifications. Recognizing the widespread influence of climate change on various aspects of socio-economic life, the study highlights the urgent need to address this global phenomenon at both global and local levels. Utilizing a comprehensive interview guide, data was collected through audio recordings and note-taking from relevant respondents. The literature review provides a detailed understanding of climate change in both a global and local context. Through meticulous analysis of the collected data, the research reveals that climate change significantly affects Swat’s residents through altered agricultural productivity, increased frequency of extreme weather events, and reduced access to essential resources. These impacts exacerbate socio-economic challenges, leading to heightened psychological stress among the community. The findings underscore the urgent requirement for proactive measures to address these challenges. The study highlights that enhancing environmental awareness, building climate-resilient infrastructure, and adopting sustainable agriculture practices are crucial. Promoting eco-friendly tourism, ensuring reliable access to resources like water and food, and strengthening healthcare and community resilience are also imperative. Investing in green infrastructure and enforcing effective policies will support adaptation efforts. Collaboration and international cooperation are essential for tackling global climate challenges, and establishing robust financial mechanisms will help fund and incentivize these climate actions. In conclusion, this research study provides a comprehensive examination of the impacts of climate change, emphasizing the need for immediate attention and concrete measures to address its effects on the people of Swat, KP. By incorporating local perspectives, the study contributes to the existing literature and informs policy formulation, guiding proactive interventions for a sustainable future.